Manual de valoración de bienes inmuebles para la Escuela de Ingeniería en Construcción del Instituto Tecnológico de Costa Rica - Mayorga-Jiménez, Ana Luisa (Instituto Tecnológico de Costa Rica, 2008)
The present project is about the elaboration of an expert report, in the specific case of the real estate. It’ll be indicated the necessary information to realize an expert's report, the steps to realize the visit of inspection and how the expert report is realized. For that, first it’ll be searched the information with different experts about the topic and is indicated which are the basic aspects to consider to establish the value of an urban area, as well as a study on the different methods of depreciation and the legal regulation that relates to the valuation of real estate. In addition, to exemplify the subjects explained in the manual some expert reports. Also are indicated the principles with that are valued the buildings and the complementary works constructed in the property that is an object of a valuation. One refers to the ethics, which is the norm that every professional one must have present on having realized an evaluation. Finally, according with the results of the investigation and the work realized during this practice, there is obtained to elaborate a manual of valuation of real estate for the course Taller II of the program of the School of Engineering in Construction.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica.Escuela de Ingeniería en Construcción, 2007.
Keywords: Costo; Fraccionamiento; Valoración; Inspección; Factores